Polarisasi Melingkar Antena Mikrostrip E Shape Dengan Pencatu Electromagnetic Coupling - Indra Surjati; Syah Alam; Saut Hotman (Jurnal Rekayasa Elektrika, 2017)
This paper proposed a new design of circular polarization E shaped patch microstrip antenna fed by proximity coupling for Wireless Fidelity applications at operating frequency of 2.4 GHz. To generate circular polarization in the proposed antenna, the next steps is making three slits on the patch antenna and with this embedded three slits produces antenna E shaped. Besides that, the proximity coupling fed line is used to increase the bandwidth of the proposed antenna. In this research the patch E shaped was put on the first substrate layer while the proximity coupling feeder was put on the second substrate layer. The substrate material used in this research is one of the two layers FR 4 Epoxy with relative dielectric constant ( r) of  4.4  and thickness (h) of 1.6 mm. The circular polarization can be achieved by adjusting the width and length of the E shaped antenna. The simulation of this research gave some important antenna parameters such as axial ratio value of 2.58 dB, return loss of -19.98 dB, VSWR of 1.223 and bandwidth of 151.3 MHz. Finally, its measurement results gave also some related comparative data such as return loss of -22.12 dB, VSWR of 1.16, bandwidth of 153.2 MHz, and Half Power Beamwidth of 580.